2014
DOI: 10.1016/j.lithos.2014.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Crystallisation of magmatic topaz and implications for Nb–Ta–W mineralisation in F-rich silicic melts — The Ary-Bulak ongonite massif

Abstract: Textural, mineralogical and geochemical data on F-rich rhyolite (ongonite) from the Ary-Bulak massif of eastern Transbaikalia help constraining the formation of magmatic topaz. In these rocks, topaz occurs as phenocrysts, thus providing compelling evidence for crystallisation at the orthomagmatic stage. Cathodoluminescence images of topaz and quartz reveal growth textures with multiple truncation events in single grains, indicative of a dynamic system that shifted from saturated to undersaturated conditions wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 45 publications
1
22
0
1
Order By: Relevance
“…Previous research indicated that the volatile fluorine is conducive to tungsten mineralization (Einaudi et al, 1981;Newberry and Swanson, 1986;Webster, 1990;Newberry, 1998;Hezarkhani et al, 1999;Chen et al, 2008;Bali et al, 2012;Che et al, 2013;Agangi et al, 2014). Theoretical modelling also proposed that fluorine could increase the electronegativity and chemical hardness of the fluid phase, which would promote the solubility of W in such a fluid phase (Vigneresse, 2009).…”
Section: Volatile Componentsmentioning
confidence: 98%
“…Previous research indicated that the volatile fluorine is conducive to tungsten mineralization (Einaudi et al, 1981;Newberry and Swanson, 1986;Webster, 1990;Newberry, 1998;Hezarkhani et al, 1999;Chen et al, 2008;Bali et al, 2012;Che et al, 2013;Agangi et al, 2014). Theoretical modelling also proposed that fluorine could increase the electronegativity and chemical hardness of the fluid phase, which would promote the solubility of W in such a fluid phase (Vigneresse, 2009).…”
Section: Volatile Componentsmentioning
confidence: 98%
“…Долгое время считалось, что вольфрамоиксиолит характерен лишь для редкометалльных пегматитов (Корнетова и др., 1982;Волошин, 1988;Suwimonprecha et al, 1995;Aurisicchio et al, 2002;Černý, Chapman, 2001;Novák et al, 2008;Melcher et al, 2017;и др.). Однако по мере освоения новых редкометалльных провинций количество его находок неуклонно растет, и в последние годы он многократно отмечен как акцессорный минерал ЛФГ и онгонитов в Европе, Африке и Азии (Johan, Johan, 1994;Chalal, Marignac, 1997;Raimbault, Burnol, 1998;Marignac et al, 2001;Kesraoui, Nedjari, 2002;Zhang et al, 2003;Перетяжко и др., 2007;Летников, 2008;Saleh et al, 2008;Agangi et al, 2014;Breiter et al, 2007Breiter et al, , 2017Melcher et al, 2017;Zhao et al, 2017;Broska, Kubis, 2018;René, 2018;Xie et al, 2018), в том числе на Дальнем Востоке России (Руб, Руб, 2006; Алексеев и др., 2010). «Лавина» находок вольфрамоиксиолита косвенно подтверждает его индивидуальность как минерального вида и позволяет считать его типоморфным минералом ЛФГ (Алексеев и др., 2010).…”
Section: обсуждение результатовunclassified
“…Topaz phenocrysts contain abundant inclusions of feldspar, aggregates of Nb-Ta-W oxide (W-ixiolite to tantalite-columbite), mica, round grains of quartz, and elongate to irregular grains of cryolithionite [Na 3 Li 3 Al 2 F 12 ]. A detailed sample description is given in Agangi et al (2014).…”
Section: Geological Setting and Sample Descriptionmentioning
confidence: 99%